Testing Methods for Masonry Cores: A way forward to increase reliability of mechanical properties evaluation - Rita Esposito; Francesca Ferretti (RILEM Technical Letters)
The assessment of unreinforced brick masonry structures and infrastructure is a worldwide challenge for the development of resilient urban areas and preservation of historical assets. Among other factors, the estimation of mechanical performance of masonry in existing construction is of importance. However, the characterisation effort does not always satisfy the requirements from structural analyses point of view, i.e. need of elastic, strength and toughness properties, and/or from technical point of view, i.e. use of conventional technical expertise and limited invasiveness. In this respect, the new RILEM Technical Committee CTM aims at promoting the use of tests on masonry cores for the evaluation of compression and shear properties of unreinforced masonry with regular units. Upon a state-of-the-art review, a database of previous experimental test series will be created to identify influencing factors (e.g., core’s geometry, boundary conditions). Selected testing procedures will be compared at various international institutes for a variety of masonry types typically used in existing structures and infrastructure. By comparing results with standardise tests, correction factors will be identified. Eventually, testing guidelines to characterise masonry with core specimens will be defined and shared within the research and engineering community.